Sokolova I. V. Representation of informational and advertising texts (on the material of the modern English language) - Sokolova I. V. (Philological Treatises, 2020)
The article represents results of research of main text-making and text-forming categories of informative- advertising text among which are integration, pragmatic orientation, addressee representation, explicit information representation, positive estimation. The definition of informative-advertising text as text-type and its ontological characteristics are given.